Penerapan Media Gambar untuk Meningkatkan Hasil Belajar IPS Materi Tokoh dalam Proklamasi Kemerdekaan - Kontan Ginting (Universitas Negeri Medan, 2017)
This study aims to determine the use of image media in improving student learning outcomes, in addition to knowing the results of student learning subjects in social studies subjects IPS In Proclamation of Independence in Class V SD Negeri 101768 in the academic year 2015/2016. The subjects of the student study consisted of 14 male students and 11 female students. Data collected through interviews, field notes and documentation. Techniques of collecting data using Tests and Observations and data analysis techniques such as Data Reduction, Data Exposure, and Data Conclusion. The results showed that the use of image media on IPS learning material of the characters in the proclamation of independence can improve student learning outcomes. This increase is indicated by the changes, previously had an average value of 51.2 with 20% classical completeness. After applying the learning approach using the image media obtained the average score of student learning result test 67.6 with 56% classical completeness. In cycle II, the average score 81,2 with 84% classical completeness. It can be concluded that the application of the image media can improve student learning outcomes in the subjects Social Science Class V SD Negeri 101768 in the academic year 2015/2016. And also from the results of this study is enough to provide motivation to students, evidenced by the learning outcomes and spirit of student learning is increased and improved.